Colonialism and decolonization in the writings of Paulo Freire - Mariateresa Muraca (University of Bologna, 2021)
The paper argues that the theme of cultural and racial oppression is present throughout Freire's work. In particular, it explores Paulo Freire's contribution to the discussion of colonialism and decolonization. To this purpose, first of all it takes into consideration some writings elaborated between the end of the 1950s and the 1970s, enhancing the dialogue with authors such as Albert Memmi, Frantz Fanon and Amílcar Cabral. Then it focuses on concepts which, although not directly linked to the analysis of colonialism, can help reinvent and expand Freire's proposal in a decolonial key. The last part is dedicated to Freire's influence on decolonial pedagogy and intercultural critical pedagogy, developed in recent decades starting from the Latin American context.